BENCHMARKING FOR BEST PRACTICES UNTUK MENINGKATKAN KINERJA ORGANISASI SEKTOR PUBLIK: SEBAGAI ALTERNATIF TRADISI ‘KUNJUNGAN’ PEJABAT LEGISLATIF DAN EKSEKUTIF - Yuyu Komariyah1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Visiting developed Kota/Kabupaten in Indonesia by DPR/DPRD members as well as by government officers has been an increasing trend. On one hand, it shows a positive side that the fast and successful development in some regions have attracted other regions to know more. However, this visit will remain only as a visit with nothing else than spending the public money without any real benefit for the sake of good governance. Therefore, in this article benchmarking for best practices which has been popular in particularly private sectors around the world and gaining more popularity in public sector is discussed as an alternative to a mere visit in order to achieve superior performance of public sector institutions.